Open versus Laparoscopic Repair of Inguinal Hernia in Aljabal Alakhdar Hospitals - Ahmad Abaidalla; Nasser Mohamed; Salma Mohamed; Esraa Abdulfatah; Amal Amhawee; Wesam Abraheem (AlQalam Journal of Medical and Applied Sciences, 2025)
Inguinal hernia presents a lifetime incidence of approximately 27% in men and 3% in women. Surgical intervention remains the standard treatment; however, there is no universal consensus regarding the optimal surgical approach. Open repair is currently the most commonly performed technique, yet concerns persist about its association with chronic groin pain. In contrast, laparoscopic repair is gaining wider acceptance due to its lower risk of postoperative pain, although the long-term recurrence rate remains uncertain. This study aims to compare the incidence of recurrence and chronic groin pain between laparoscopic and open repair techniques for inguinal hernia. It is designed as a retrospective cohort study conducted within the Department of Surgery across multiple hospitals in the AljabalAlakhdar region, including Albyeda Medical Center, Cyrenaica Hospital, and Alfarabey Clinic. Data collection was carried out by the authors using the hospital health informatics system, covering the period from January 2023 to December 2024. This timeframe was selected based on the availability of patient records and statistical data.The study population included all patients aged 18 years and above who underwent inguinal hernia repair during the specified period. Patients younger than 18 years and those who underwent repair for other types of hernia, such as ventral hernia, were excluded. The primary objective was to evaluate the comparative effectiveness of open versus laparoscopic repair, with particular attention to recurrence rates and postoperative complications. Given its reduced risk of complications and shorter recovery time, laparoscopic repair is increasingly favored over the traditional open approach.